Mesenchymal stem cells in human meniscal regeneration: A systematic review. (December 2017) - Chew, Ernest; Prakash, Rohan; Khan, Wasim
Abstract: Background: Stem cell regeneration is the holy grail of meniscal tissue repair. Currently, the best treatment is to preserve the original meniscus but if it fails, a partial meniscectomy is indicated to delay the onset of osteoarthritis. Materials and methods: The authors present a systematic review to determine the up-to-date evidence underlying the use of mesenchymal stem cells for meniscal regeneration in humans. A search was conducted using the electronic databases of MEDLINE/Pubmed, Google scholar, and the Cochrane Collaboration. Search keywords included human, meniscus, stem cells and regeneration. Results: After screening 10 non-duplicate studies, 5 were identified based on title and abstract. 4 were included in the analysis. There were marked differences in the method of stem cell harvest techniques. 3 studies administered stem cells through percutaneous injection into the knee and 1 study used a collagen scaffold. MRI analysis, functional scores and safety were assessed and the longest follow-up period was 2 years. The Visual Analogue Score (VAS) was most commonly used to assess function and patients generally showed an improvement. There were no reported adverse events. Conclusion: Despite positive results from animal models, there is currently a lack of evidence in humans to conclude that stem cells can form durable neotissue similar to original human meniscus. There is a need for standardisation of protocol before further trials are considered. Initial outcomes from human studies are promising and mesenchymal stem cells may play an important role in meniscal repair in years to come. Highlights: Current evidence for stem cell therapy in meniscal repair is in its early stages. There is a need for standardised protocol before further trials are considered. The human studies suggest stem cells have potential for meniscal regeneration.